Faktor yang Mempengaruhi Kepatuhan Masyarakat terhadap Protokol Kesehatan di Masa Pandemi Covid-19 - Lipstiani, Winda; Rahmawati, Dina (Faletehan Health Journal, 2022)
The increase of COVID-19 cases was accompanied by a decrease in the level of community compliance with health protocols thereby increasing the prevalence of COVID-19 cases. The purpose of this study was to determine the factors that influence community compliance in implementing health protocols during COVID-19 pandemic in the working area of Cimarga Health Center, Lebak Regency. The research design used cross-sectional. The research samples were 96 respondents selected by using probability sampling cluster sampling technique. The research instrument used a questionnaire which the validity and reliability were tested by Cronbach’s alpha value of 0.760. The data analysis used chi-square test. The results showed that in implementing health protocols most of the respondents were disobedient (52.1%), had less knowledge (54.2%), had a negative attitude (53.1%), and were less motivated (57.3%). There was a significant relationship between knowledge (p value = 0.001), attitude (p value = 0.015), and motivation (p value = 0.016) with community compliance in implementing health protocols. The community was expected to increase their knowledge of health protocols to encourage compliance with health protocols to prevent COVID-19.